Analisis Biaya dan Nilai Utilitas pada Pasien Hemodialisis yang Diberikan Terapi Erythropoiesis di Rumah Sakit - Madania Madania; Tety Sutriyati Tuloli; Nur Rasdianah; Juliyanty Akuba (Indonesian Journal of Pharmaceutical Education, 2021)
Chronic kidney failure is a condition where there is a gradual decline in kidney function. Chronic kidney disease is often followed by complications of anemia. The use of erythropoietin therapy in chronic renal failure patients undergoing hemodialysis requires no small amount of money. This affects the quality of life (utility). The purpose of this study is to measure costs and utility values using the EQ-5D-5L (EuroQol-Five Dimensions) instrument, VAS (Visual Analog Scale), and costs based on the patient's perspective at Prof.Aloei Saboe Hospital. This study is a prospective cross-sectional approach. Data was collected using the EQ-5D-5L and EQ-VAS questionnaires. The subjects of the study were hemodialysis patients as many as 45 met the inclusion criteria. The results showed that the most widely used Erythropoietin therapy was single Hemapo. The results of the calculation of the estimated cost of each hemodialysis patient from the perspective of a patient for one month of therapy are Rp. 7,112,000. The average expenditure of patient transportation costs is Rp. 50,111. The average cost of food for the patient is Rp. 25,000.Utility value based on average Indonesian set value 0.673 (sufficiently feeling well)and VAS score 71.4 (health status is quite healthy).